Are You Unhappy Having Minority Co-Workers? - Getinet Astatike Haile (Institute for the Study of Labor (IZA), 2013)
This paper attempts to establish empirically whether natives' job satisfaction is adversely affected by having minority co-worker(s). The paper uses nationally representative linked employer-employee data and eight different facets of job satisfaction. Measuring minority co-worker status at the workplace- and occupation-level and employing alternative econometric estimators; the paper finds that on average natives' experience a reduction in job satisfaction due to having minority co-worker(s). The effect found is larger if the co-worker-ship is at the occupation-level.
Keywords: J7; J15; J82; I31; 330; discrimination; job-related well-being; linked employer-employee data; Britain